2017
DOI: 10.3892/etm.2017.4776
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the roles of house dust mite allergens, ovalbumin and lipopolysaccharides in the sensitization of mice to establish a model of severe neutrophilic asthma

Abstract: Neutrophilic asthma (NA) is associated with a severe disease course and poor response to corticosteroids. The present study aimed to compare the effects of various concentrations of house dust mite (HDM) allergens, ovalbumin (OVA), the major egg allergen, and lipopolysaccharide (LPS) in combination on the onset of severe NA. Female C57BL/6 mice were grouped according to a random number table and intranasally sensitized with HDM/LPS/OVA extracts on days 0, 1 and 2 of the study. In group 1, mice received 50 µg H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…In murine asthma models, LPS or HDM administration via the airways increased Th17 cell response and the production of IL-17 [ 15 ]. In a previous study, we showed that 100 μg HDM + 100 μg OVA + 15 μg LPS was successful for establishing a neutrophils-dominant asthma [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In murine asthma models, LPS or HDM administration via the airways increased Th17 cell response and the production of IL-17 [ 15 ]. In a previous study, we showed that 100 μg HDM + 100 μg OVA + 15 μg LPS was successful for establishing a neutrophils-dominant asthma [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This shows that neutrophilic asthma mice primarily exhibited Th17 cell differentiation, and the recruitment of neutrophils, thus promoting the development of asthma. And the data in detail was published by our team [ 26 ].MBD2, a DNA methylation regulation element, can regulate T cell differentiation [ 27 , 28 ]. Although little is known about epigenetic regulation in neutrophils-dominant asthma, in our study we report that MBD2 expression in splenic CD4 + T cells and lungs from neutrophils-dominant asthma mice was significantly higher compared to conventional asthma mice and the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The ethology of the mice was evaluated by observation of the following parameters: Fur luster, touching of nose and scratching of ears, irritability, sneezing, rapid breathing and incontinence ( Jia et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Despite accumulating evidence of their role in human asthma, the function of MCs in mouse models of allergic airway inflammation is still a matter of controversy, with several contradicting results. A source of variation in the published literature derives from the route/regimen of immunization and the choice of allergen, [41][42][43][44] but the main difficulty in reaching conclusive results stems from the use of Kit mutant mice. These animals lack MCs but show several additional alterations compared to wild-type mice that complicate interpretation of results.…”
Section: Discussionmentioning
confidence: 99%